Correlation without a cause: an epidemiological odyssey. (3rd April 2020) - Davey Smith, George; Phillips, Andrew N
Background: In the 1980s debate intensified over whether there was a protective effect of high-density lipoprotein cholesterol (HDL-C) or an adverse effect of triglycerides on coronary heart disease (CHD) risk. In a 1991 paper reprinted in the IJE we suggested that the high degree of correlation between the two, together with plausible levels of measurement error, made it unlikely that conventional epidemiological approaches could contribute to causal understanding. The consensus that HDL-C was protective, popularly reified in the notion of 'good cholesterol', strengthened over subsequent years. Reviewing the biostatistical and epidemiological literature from before and after 1991 we suggest that within the observational epidemiology pantheon only Mendelian randomization studies—that began to appear at the same time as the initial negative randomized controlled trials—made a meaningful contribution. It is sobering to realize that many issues that appear suitable targets for epidemiological investigation are simply refractory to conventional approaches. The discipline should surely revisit this and other high-profile cases of consequential epidemiological failure—such as that with respect to vitamin E supplementation and CHD risk—rather than pass them over in silence.